Green Logistics development and evaluation of the carbon footprint - Guan, xin (My University, 2015)
Along with the worldwide climate changing, human activities and the rapid deterioration of the environment, Low-carbon economy in recent years become increasingly focus of attention in people's lives. The economic reform will gradually penetrate into the logistics system, modern logistics as a composite service industry, play a decisive role in the modern division of labor and cooperation under the social environment, it is a manufacturing! The important supporting business is an important bridge between production and consumption. The logistics industry is in a period of rapid development, the logistics process not only energy consumption demand is big, and the C02 emissions are also large. Coupled with the destruction of the human living environment, the greenhouse effect becomes more and more prominent, more the need of the development of green logistics, low carbon logistics. However, at home and abroad for most of the research of this aspect is still stay in the stage of qualitative analysis, quantitative analysis of the literature on energy consumption and C02 emission of less amount of logistics system. There are four objectives will be discussed. The first objective is the relevant literature on the green logistics is summarized, which lays the foundation for the research in this paper, green logistics. The second objective is the energy consumption and C02 calculation models were summarized, to provide reference for other scholars to conduct relevant research. The third objective is through statistical analysis, master the different modes of transport energy consumption and C02 emissions, and provide the basis for enterprises to choose the mode of transport. The fourth objective combining with specific examples, analyzed the carbon footprint of the logistics process instance modeling based on LCA.
Keywords: Carbon footprint; Logistics enterprises; Green logistics; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|